EDUKASI DAN SIMULASI BENCANA TERHADAP KEMAMPUAN PENGENALAN RISIKO DAN PENYELAMATAN DIRI ERUPSI GUNUNG FASE MITIGASI - Nurul Laili (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Disaster conditions require handling and rescue efforts so disaster mitigation skills, risk recognition and self-rescue are needed. Disaster education and simulation are one way to improve skills and reduce the impact of disasters Purpose: The purpose of this study was to determine the effect of disaster education and simulation on the ability to recognize risks and self-rescue for volcanic eruptions in the mitigation phase of students at SMAN 1 PlosoklatenMethods: The design of this study was a pre-experimental design with a one-group pre-test and post-test design approach. The population of this study was 350 and a sample of 105 respondents was obtained. The sampling method used a purposive sampling technique and data was analyzed using the Wilcoxon testResult: Before the intervention, most respondents had poor skills (71.4%) and after the intervention, almost all respondents had good skills (92.4%). Data analysis obtained the results of the study ρ value <0.001 (α = 0.05), there was an effect of disaster education and simulation on the ability to recognize risks and self-rescue for volcanic eruptions in the mitigation phaseImplication: Providing education and simulation can improve the abilities of respondents. The higher a person's ability, the more prepared they are to face disasters. It is recommended that the community improve their knowledge and abilities in disaster management through active participation in disaster training activities